VD_FINDINFO HC / 2013 / 632 vom 19. September 2013 - VD Tribunal cantonal (2013)
REMARIAGE, SALAIRE, RÉDUCTIONEN GÉNÉRAL, MESURE PROVISIONNELLE, MODIFICATIONEN GÉNÉRAL, JUGEMENT DE DIVORCE | 129 al. 1 CC, 261 CPC (CH)